(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the predictors of in hospital mortality in gastro esophageal variceal (GEV) hemorrhage/bleeding in patients of chronic liver disease. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the gastroenterology department of Nishtar hospital, Multan in duration of one year from March 2019 to March 2020 in one-year duration. Materials and Methods: A total of Two hundred and sixty patients were enrolled in present study. Clinical signs and laboratory investigations were correlated for prediction of in hospital mortality. Most common laboratory investigations include serum bilirubin and creatinine and clinical parameters were bleeding within 24 hours after endoscopy, ascities and Child-Pugh score. Data analysis was done by using SPSS version 23. Results: In our study Hemoglobin was found deranged in 5.2% patients, prothrombin time in 7.6%, S. bilirubin in 4.8%, S. creatinine in 8.7% and S. albumin in 2.6% of the survivors Similarly hemoglobin was found in 10%, prothrombin time in 3.3%, S. bilirubin 6.7%, S. creatinine 6.7% and S. albumin in 3.3% of the non-survivors. Differences was calculated statistically insignificant. Conclusion: Deranged serum creatinine, serum bilirubin, PSE and re-bleed within 24 hours of endoscopy were independent predictors of in hospital mortality. Aggressive control on laboratory and clinical values with latest innovative management is helpful in reduction of in hospital mortality.